2019
DOI: 10.1172/jci.insight.124865
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body composition and weight during the menopause transition

Abstract: BACKGROUND. The relation between the menopause transition (MT) and changes in body composition or weight remains uncertain. We hypothesized that, independent of chronological aging, the MT would have a detrimental influence on body composition. METHODS. Participants were from the longitudinal Study of Women's Health Across the Nation (SWAN) cohort. We assessed body composition by dual energy x-ray absorptiometry. Multivariable mixed effects regressions fitted piece-wise linear models to repeated measures of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
209
5
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 243 publications
(234 citation statements)
references
References 50 publications
15
209
5
5
Order By: Relevance
“…The hormonal changes in menopause are known to lead to bone loss through increased bone turnover with a net deficit in the bone formation relative to bone resorption [ 4 , 5 ]. Several studies have also suggested that menopausal hormonal changes have an effect on the decline in muscle mass among middle-aged women [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hormonal changes in menopause are known to lead to bone loss through increased bone turnover with a net deficit in the bone formation relative to bone resorption [ 4 , 5 ]. Several studies have also suggested that menopausal hormonal changes have an effect on the decline in muscle mass among middle-aged women [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women also experience an accelerated progression of subclinical atherosclerosis during the menopausal transition [6, 7]. The steeper increase in atherosclerotic risk during the menopausal transition is likely explained by the associations between menopause and changes in cardiometabolic risk factors, including increases in total fat and visceral fat [8, 9], and elevations in total cholesterol and low-density lipoprotein (LDL) cholesterol [10]. These adverse changes, which go beyond the effects of chronological aging alone [810], may be preventable by lifestyle modifications [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well-known vasomotor symptoms [2] and accelerated bone loss [3], MT significantly alters body composition with opposite effects on fat and lean body mass [4]. The Study of Women’s Health Across the Nation cohort, which followed longitudinally 1246 women of different ethnic backgrounds, confirmed that both the accelerated fat mass (FM) gain and the decline in lean mass are menopause-related and not merely age-dependent [5]. Several small interventional studies evaluated whether these changes are reversible with menopausal hormone therapy (MHT) and by what mechanisms [6].…”
Section: Introductionmentioning
confidence: 99%